Widespread introduction of market mechanisms in developing cooperative relations in agriculture in Uzbekistan - Hadjimuradovich, Burkhanov Alisher ,; Turdikulovich, Sattorkulov Obidkul ,; Baboevich, Mukhametov Abubak; Raushanovich, Umaraliev Olimjon; Musurmanovich, Urazmatov Jonibek; Uktam, Kholikulov Jamshid; Abulhayevich, Obidov Rasul; Abdulazizovich, Abduvohidov Akmal; Xolmuradovich, Shoyev Olim; Xusanovich, Maxmudov Sherali (International Journal of Psychosocial Rehabilitation, 2020)
The method of prediction is the use of the system of co-operative and integrated systems in agropromyshlennom complementary, which is the objective of the objective mindset of the current, the practical and the non-negotiable. monographicheskogo, abstract-logicheskogo, economical-statisticheskogo, methodical analogues and organizational-economics.Theoreticheskoye and methodological equipments in the region and region of the cooperative and agro-economical integration. Сушчественный вклад в разработку наочных основь развития selskoxozyaystvennoy cooperatives в переходный ученные: А. A. Nikonov, I. N. Buzdalov, V. D. Martynov, A.. V. Petrikov, E. V. Serova, G. I. Schmelev, R.. G. Janbyx. Возрождая насочное насление А. V. Chayanova, N. D. Kondratyeva, M. I. Tugan-Baranovskogo и других русском ученых и cooperatives In many developed countries, agriculture is predominantly farming. In a number of countries, 100% of farms provide this type of activity. Farms are merged into cooperatives to increase efficiency. Cooperative is a special tool to help improve economic performance. Analysis of the best practices in the production, storage, processing and sale of fruit and vegetable production in Uzbekistan demonstrates the need for effective stimulation of cooperation among producers of these products.